2017
DOI: 10.4267/2042/62668
|View full text |Cite
|
Sign up to set email alerts
|

LATS1 (Large Tumor Suppressor 1)

Abstract: LATS1 tumor suppressor is a serine/threonine kinase of the AGC kinase family and a core component of the Hippo pathway in mammals. LATS1 regulates various biological processes such as cell cycle progression, genetic stability, cell motility and adhesion, apoptosis, stem cell renewal and differentiation (Visser and Yang, 2010;Mo et al., 2014). LATS1 performs these functions by phosphorylating various substrates such as transcriptional coactivators YAP and TAZ (Zhao et al., 2007; Hao et al., 2008).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Large tumor suppressor 1 (LATS1)is a highly conserved serine/threonine kinase and a key player of the Hippo pathway in mammals.As a tumor suppressor, LATS1 loss or mutation is most closely associated with tumorigenesis and progression of various human cancers, including bladder cancer (4)(5)(6)(7)(8)(9)(10).But the latest studies showed that deletion of LATS1/2 in tumors thus enhances anti-tumor immune responses via the activation of TLRs-MYD88/TRIF pathway, stimulating anti-tumor responses of an immunecompetent host (11). And the loss of LATS1/2 prevents the growth of murine colon adenocarcinoma MC38 cells (12).…”
Section: Introductionmentioning
confidence: 99%
“…Large tumor suppressor 1 (LATS1)is a highly conserved serine/threonine kinase and a key player of the Hippo pathway in mammals.As a tumor suppressor, LATS1 loss or mutation is most closely associated with tumorigenesis and progression of various human cancers, including bladder cancer (4)(5)(6)(7)(8)(9)(10).But the latest studies showed that deletion of LATS1/2 in tumors thus enhances anti-tumor immune responses via the activation of TLRs-MYD88/TRIF pathway, stimulating anti-tumor responses of an immunecompetent host (11). And the loss of LATS1/2 prevents the growth of murine colon adenocarcinoma MC38 cells (12).…”
Section: Introductionmentioning
confidence: 99%